Presencia de microplástico derivado de la degradación de tanques de reserva plásticos en el agua potable de Riobamba - Chávez Carrillo, Brayan Alejandro (2019)
The present is an exploratory study, which is intended to evaluate the presence of fibers of micro plastics derived from the degradation of high-density polyethylene (HDPE). Material from which the drinking water reserve tanks in Riobamba city were commonly made, this analysis was carried out having a typical population, and on a representative sample, sampling of the water contained directly in the reserve tanks was carried out, applying the INEN 1108 Potable Water Standard. Requirements 250 ml of each of these samples was filtered in a laminar flow chamber, to then examine the filters with an optical microscope. Applying pink pigment of flare on these to help the identification of the particles or fibers of micro plastics, obtaining a result that all samples belonging to tanks with more than five years of useful life have the presence of microplastic.